Kashef Chowdhury : a glass labyrinth in Venice - Chowdhury, Kashef; McCarter, Robert, 1955-; Aravena Mori, Alejandro; Chenal, Eric; International Architectural Exhibition 2016 : Venice, Italy) (Zurich, Switzerland : Park Books AG, 2018)
Over the past years, Dhaka-based architect Kashef Chowdhury has become renowned for a body of work that responds with great sensitivity to places, local circumstances, and the demands of a building's users. At the 2016 International Architecture Exhibition of the Venice Biennale, Chowdhury presented four recent projects his firm URBANA has realized in Bangladesh in a fascinating exhibition, which he has designed with equal sensitivity and care. The labyrinth is an age-old space of intrigue, discovery and accident, which has fascinated architects throughout history. For his installation in Venice, Chowdhury challenged spatial perceptions by a simple turn: the labyrinth, which hides and blocks, suddenly becomes transparent. Notwithstanding the obvious reference to Venetian glass, the labyrinth retains, or even accentuates, a sense of spatial disorientation. The installation was conceived not merely as a hyper-maze but rather as an expression of the anxiety that the artist experiences in his work due to a myriad of uncertainties. From design to construction, funding to maintenance, the part of the world where URBANA chiefly works presents itself with challenges at every turn, and it is in this milieu that an architect must operate with firm resolve. Chowdhury's Glass Labyrinth in Venice seems to explicate the notion that, although an architect has a clear vision of what he he wants to do, the path to achieving that in the environment he operates, is with laden with perplexing barriers. This new book explores and documents Kashef Chowdhury's intriguing installation in Venice in beautiful photographs by Eric Chenal and with an illuminating text by Robert McCarter.
"The Glass Labyrinth was an installation by Kashef Chowdhury / URBANA titled To Live Is to Be Slowly Born, in the Central Pavilion in the Giardini as part of the 15th International Architecture Exhibition of La Biennale di Venezia"--Colophon.
Includes bibliographical references.
ARC
Keywords: Chowdhury, Kashef -- Exhibitions; Architecture -- Bangladesh -- Exhibitions; Installations (Art) -- Italy -- Venice -- Exhibitions